Saturday

April 19, 2014

April 19, 2014

Posted by **kingwendu** on Saturday, December 17, 2011 at 8:15am.

- polynomial -
**Steve**, Saturday, December 17, 2011 at 4:05pm(cx-d)(2x^2 - 3x - 2) = ax^3 - 11x^2 + bx + 2

2cx^3 - (3c+2d)x^2 - (2c-3d)x + 2d = ax^3 - 11x^2 + bx + 2

2c = a

3c+2d = 11

2c-3d = -b

2d = 2

so,

d=1

3c+2=11

c=3

-3 = b

a = 6

check:

(3x-1)(2x^2 - 3x - 2) =

6x^3 - 11x^2 - 3x + 2

**Related Questions**

Calculus - Suppose that ax^2 + bx + c is a quadratic polynomial and that the ...

POLYNOMIALS - The cubic polynomial f(x) is such that the coefficient of x^3 is -...

Math ( Polynomial ) - This time three questions - 1. If (x^2 - 1 ) is a factor ...

Math ( Polynomial ) - This time three questions - 1. If (x^2 - 1 ) is a factor ...

Calculus - A cubic polynomial function f is defined by f(x) = 4x^3 + ax^2 + bx...

Calculus - A cubic polynomial function f is defined by f(x) = 4x^3 + ax^2 + bx...

maths - Given the identity x^4-2x^3+ax^2-2=x(x-1)(x+1)Q(x)+4x^2+bx+c , where Q(x...

Calculus II - 1) Compute the indefinite integral: integral 2x ln(x^2 - 8x + 18) ...

Math - I've been staring at this problem for an hour and have NO IDEA WHAT TO DO...

Calculus - Which of the following would have a horizontal asymptote of y = b/a? ...